Perception of Urban Residents towards Drinking Water Quality and Supply: A Case of Varanasi City - Pandey, Richa; Singh, Jagadish (National Geographical Journal of India, 2022)
Ensuring a safe and continual water supply is of utmost importance as the health and well-being of individuals and society very much depend on it. Adequate supply of water of requisite quality for drinking, bathing, cooking etc is closely linked with personal hygiene and public health. The water requirement for different activities varies with life style, culture, diet and wealth. Therefore, it must be distributed judiciously among the consumers for varied uses. Economic growth of a city largely depends on a water supply system capable of supplying sufficient quantity of potable water to all residents. Rapid growth of population, particularly in urban areas has exerted tremendous pressure on water supply. On the one hand, demand for water has been continuously rising in urban areas due to change in life style; on the other hand ground water potential is declining due to overexploitation and expansion of concrete structures over the years. As a result, city authorities find difficulty to provide adequate quantity of good water to their residents. Keeping the aforesaid in view, the present paper attempts to analyse empirically the responses and reactions of residents in respect to drinking water quality and supply in Varanasi- a million + city of India. For this study, 700 persons from various cross-sections of society and space were selected and interviewed with the help of a questionnaire. The results of such survey can be of much help to municipal authorities in decision making to ensure sufficient safe water to all urban residents including the very poor.